PENGARUH PENAMBAHAN BUBUK JAHE EMPRIT (Zingiber officinale Var. Amarum) TERHADAP KARAKTERISTIK TEH DAUN KELOR (Moringa oleifera) - Wisakarani, Ni Putu Ayu; Timur Ina, Putu; Ekawati, I Gusti Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2016)
This research has been conducted in order to know the effect of ginger powder ( Zingiber officinale Var. Amarum) addition on the characteristic tea of Moringa oleifera leaves. The experimental design used in this research was a completely randomized design with the treatment of 5 levels of percentage of ginger powder which consist of 0%, 2%, 4%, 6%, and 8%. The whole treatment was repeated three times to obtain 15 units of experiment. Data were analyzed by analysis of variance and if there significant effect on the observed variables, then followed by Duncan multiple range test. The result showed that the treatment of ginger powder effected significantly (P<0,01) on antioxidant capacity, Vitamin C, color, aroma and flavor (by score test). The best result was obtained on treatment of addition of ginger powder with concentration of 8% with the characteristic of product such as :  5.53% moisture, 26,82  mg/100g GAEAC, 5,42 mg/100 ascorbic acid, aroma on hedonic test is slightly like, aroma on scoring test is ginger flavor, taste on hedonic test is like, taste on scoring test is ginger taste, color and the overall acceptance are like.
Keywords: moringa, ginger, antioxidant capacity, Vitamin C, moringa leaves tea